Improving an existing SAP system with an additional graph database - Babak, Mariia; Dudáš, Marek; Nguyen, Viet Bach; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The master thesis investigates the possibilities of graph databases for the Order-to-cash business process. The thesis aims to assess the comparative effectiveness of graph databases versus traditional relational databases and develop and implement proof of concept for graph database solution based on SAP ERP logic. This solution includes enhancing the ability to analyze and visualize complex data relationships by applying graph database technology. The thesis describes the development and challenges of implementing a new graph database solution using Neo4J to enhance monthly reporting for existing firm. This includes the creation of data architecture, nodes and edges schema, and an ETL pipeline implemented in Python. The features of the Neo4J tool demonstrate the functionality focusing on visualization analysis of the newly developed solution. As an example of Cypher query possibilities, this work uses recommendations analysis, which shows the potential for further analytical capabilities. The thesis concludes with testing the solution with employees using the System Usability Scale method and suggests future improvements for integrating the SAP system with the developed graph database. The final sections reflect on the implications of the findings and propose areas for further research.
Vedoucí práce: Marek Dudáš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses